Experiences, Benefits, and Challenges of Virtual Teamwork for Public Libraries in the US Midwest during the COVID-19 Pandemic / Singh, K., & Bossaller, J. S. (2022). It’s just not the same: Virtual teamwork in public libraries. Journal of Library Administration, 62(4), 512–534. https://doi.org/10.1080/01930826.2022.2057130 - Opuda, Eugenia (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objective – To learn about public libraries’ transition to virtual teams before and during the COVID-19 pandemic, and to uncover the benefits, as well as challenges, of using technology and tools for virtual teamwork.Design – Qualitative, online, semi-structured interviews with thematic analysis of data.Setting – Public libraries in the midwestern United States.Subjects – Eight leaders of public libraries or library systems and a state library.Methods – The authors conducted a snowball sampling technique to recruit participants in the midwestern United States. Through 30-60 minute Zoom sessions, the authors conducted interviews with the study participants. Each session was led by one interviewer and a note-taker and all interviews, with one exception, were recorded. Interviewers relied on an interview protocol, shared in the appendices of the paper, that addressed demographic questions as well as questions related to the study objectives. The authors comment that they reached data saturation after conducting interviews with eight subjects and decided to stop recruitment. Using the notes from the interview and Zoom session transcripts, the authors individually analyzed the data and then collectively discussed the themes as well as similarities and differences of participant responses.Main Results – Study respondents were mid- to late-career professionals in medium to large organizations. All respondents were white and a majority were women (n = 6) with only two men. A majority (n = 7) had a Master’s degree in Library and Information Science, and one had a PhD in a related field. Thematic analysis of the eight interviews uncovered several broader themes, including changes to staffing structures during the pandemic, the adoption of new technologies, the impact and experiences of using new technologies, the implementation of remote work, and the changes in services during the pandemic. Prior to the pandemic, library staff were involved in a variety of teams at various levels, including within the library, among consortia, and even throughout community organizations. These teams continued to meet during the pandemic using various technologies. The COVID-19 pandemic created the need to create new teams quickly to address safety protocols and the continuation of library services. Many libraries closed their physical locations during the pandemic with many in-person services offered digitally or re-envisioned to comply with current safety protocols. Technology adoption varied depending on the size of the library and the ease of use and familiarity with certain tools. Many teams adopted video conferencing tools to continue to meet as a group, platforms to share documents, and messaging apps to enhance group communication. Some libraries applied for grant funding to expand their technology access or digital services. Though there was widespread adoption of technology, libraries prioritized communication among their teams, which resulted in less emphasis on technology security and privacy.Benefits of the adoption of new technologies were enhanced participation and accessibility at team meetings and virtual programming, expansion in skill development and training for staff, and the ability to continue working while adhering to COVID-19 safety protocols. Teams were able to meet virtually across multiple locations, and the online format of meetings allowed for more equitable participation among attendees. Travel costs and travel time were eliminated, and the online meeting chat feature ensured that typically quieter participants could engage with the conversation. Additionally, libraries were able to host larger library programs online by eliminating travel cost and time. The COVID-19 pandemic created the need for rapid team formation in order to address safety protocols, ensure continuity of library services, and support the use of digital services. Challenges included a steep learning curve for some staff using new technologies, a lack of access to adequate devices or broadband for library workers living in rural areas, the development of virtual meeting fatigue leading to disengagement, and a lack of a sense of community. Though many libraries embraced remote work, front line staff were still expected to return to work physically. While remote work helped in some ways, it also presented a challenge for staff who did not have quiet spaces to focus, appropriate work setups at home, or consistent access to good internet.Conclusion – The COVID-19 pandemic forced many libraries to adapt quickly to a new environment of digital and hybrid teamwork while still attempting to maintain community-oriented services. Library leaders explored how flexible working environments could enhance employee engagement by using technology and addressed many challenges in adopting new technologies and making them accessible for staff. As well, library leaders addressed staff morale by extending grace to staff members, providing professional development in new areas of librarianship, and creating scheduling shifts for remote and in-person work. Many organizations returned to physical meetings when it became safe to do so but also continued to offer hybrid work options and use some technology adopted during the pandemic. The pandemic required flexible and creative problem solving. The experience enabled library leaders to identify the benefits and challenges of adopting new technology, maintaining service continuity, emphasizing the need to think about information security, and adapting and creating teams as needed.